2017
DOI: 10.1038/s41598-017-08208-2
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive motor cortex stimulation reinforces the pain modulation circuits of peripheral neuropathic pain

Abstract: Recent evidence indicates that motor cortex stimulation (MCS) is a potentially effective treatment for chronic neuropathic pain. However, the neural mechanisms underlying the attenuated hyperalgesia after MCS are not completely understood. In this study, we investigated the neural mechanism of the effects of MCS using an animal model of neuropathic pain. After 10 daily sessions of MCS, repetitive MCS reduced mechanical allodynia and contributed to neuronal changes in the anterior cingulate cortex (ACC). Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Repetitive TMS [49] and fMRI [50] studies documented that patients suffering from chronic pain presented with altered spinocortical and intracortical excitability of primary motor cortex, that could contribute to the impairment of their motor performance and the limited modulation of chronic symptoms related to the pain condition [51]. Recent studies [52] on animal models, confirmed that the repetitive stimulation of motor cortex is able to modify synaptic connections involved in pain control, with an adjustment of mechanical hypersensitivity occurring in neuropathic pain. Activation of the motor cortex has an analgesic effect on pain conditions [53], but the motor cortical dysfunction that seemed to characterize FM patients could reduce the modulating effect on pain.…”
Section: Reduced Motor Performance and Motor Cortical Areas Activatiomentioning
confidence: 99%
“…Repetitive TMS [49] and fMRI [50] studies documented that patients suffering from chronic pain presented with altered spinocortical and intracortical excitability of primary motor cortex, that could contribute to the impairment of their motor performance and the limited modulation of chronic symptoms related to the pain condition [51]. Recent studies [52] on animal models, confirmed that the repetitive stimulation of motor cortex is able to modify synaptic connections involved in pain control, with an adjustment of mechanical hypersensitivity occurring in neuropathic pain. Activation of the motor cortex has an analgesic effect on pain conditions [53], but the motor cortical dysfunction that seemed to characterize FM patients could reduce the modulating effect on pain.…”
Section: Reduced Motor Performance and Motor Cortical Areas Activatiomentioning
confidence: 99%
“…no. 38450; Ugo Basile, Gemonio, Italy) [ 15 ]. Briefly, rats were placed individually in plexiglass boxes equipped with a wire mesh floor to acclimate to the testing environment for 10 min, or enough time to cease exploratory behavior.…”
Section: Methodsmentioning
confidence: 99%
“…A hole was made in the skull overlying the M1, and custom-made insulated bipolar platinum electrodes (height, 70 μm; exposed tip, 50 μm; distance between electrodes, 500 μm) were applied epidurally above the M1 at stereotaxic coordinates determined from previous MCS experiments (anterior, 1.8 mm; lateral, 2 mm), contralateral to the nerve injury site (Fig. 1A) 61 . The stimulation electrodes for MCS were held in place with two bone screws and dental cement.…”
Section: Stimulation Electrode Implantationmentioning
confidence: 99%